Cucurbit Powdery Mildew Race Identification by Triplet-Septet and Disease Progress Estimation - de Oliveira Rabelo, Hudson [UNESP] (2023)
The Triplet-Septet (TS) set of melon cucurbit powdery mildew (CPM) race differentials (CPMRD) was established to provide an international means for objective and uniform identification and designation on CPM races. The Area Under Disease Progress Stairs (AUDPS) method for disease progress estimation was derived from the Area Under Disease Progress Curve (AUDPC) method, and both have been used to evaluate disease progress on other crops. We aimed to identify a melon CPM race on the TS melon CPMRD, and estimate disease progress thereon using AUDPC and AUDPS. Plants were inoculated at the 3 to 4 true leaf stage. Severity of CPM infection was evaluated on the 21 TS melon CPMRD at 15, 22, 32, and 41 days after inoculation (DAI) using a visual scale. The CPM population in the greenhouse was identified as race S based on reactions of a set of 11 commonly used melon CPMRD, and it may also be designated as 127.127.126 on the TS melon CPMRD. AUDPS identified higher levels of disease than AUDPC, and its results agreed with those obtained by the commonly used melon CPMRD conventional race identification methods (current and Triplet-Septet). AUDPS can be used to evaluate the disease progress on CPM